Exopolysaccharides from Prokaryotic Microorganisms-Promising Sources for White Biotechnology Processes - (:unkn) unknown (Elsevier, 2015)
Exopolysaccharides (EPSs) synthesized by microorganisms suggest unique properties and advantages in their exploration and are an attractive alternative of plant, algal, and synthetic polysaccharides. They are produced in large-scale environmentally friendly fermentations; their nontoxicity and biodegradability suggest their exploration in variety of white biotechnology processes leading to resolving of ecological problems. Although the large number of new polymers was described in last decades, still their capacity for utilization is underestimating. An objective of this article is to provide basic information on the chemical structure of prokaryotic EPS; their physiological roles in the cell; mechanisms for their synthesis and genetic approach for improving the yield and modification of EPS; functional properties and applications of commercially important EPS in the field of food, agriculture, cosmetics, oil, and medical industries. The prospects for application of new polysaccharides and their potential for commercialization are emphasized. © 2015 Elsevier B.V. All rights reserved.
Keywords: Cell functions; EPS advantages; EPS structure; Market-valued EPS; Polysaccharide expression; Prokaryotic exopolysaccharides; Synthetic pathways production conditions